Application of the finite-element method for determining the stiffness of rolling bearings - Sławomir BUCKI; Grzegorz PERUŃ; Bogusław ŁAZARZ (Transport Problems, 2008)
The paper presents the results of numerical tests performed with use of the FEM method, the aim of which was determining the stiffness of the outer raceway - rolling element - inner raceway system of bearing 6307. The characterization obtained has been compared with a characterization determined with analytical methods and in the next stage, it will be used to determine the total stiffness of the bearing, variable in working time. Correct modelling of bearing stiffness is one of important conditions for obtaining correct results of simulation calculations. Obtained results will allow the determination of possibilities of limiting vibroactivity of toothed gears, commonly used in transport.